Implementation of an Early Discharge Protocol and Chest Pain Clinic for Low-Risk Chest Pain in the Emergency Department. Issue 1 (March 2018) - Kashef, Mohammad Amin; Garb, Jane; Kugelmass, Aaron; Lotfi, Amir
Abstract : Background: Most of the patients presenting to emergency department with chest pain are at low risk of adverse events. Identifying high-risk patients can be challenging and resource intensive. Methods: We created a protocol to assist early discharge of low-risk adults with chest pain from emergency department. Also a chest pain clinic (CPC) was started for cardiology follow-up within 72 hours. In a retrospective cohort study, primary outcome of major adverse cardiac events (MACEs) of death, myocardial infarction, or revascularization was compared between CPC patients and those hospitalized for observation. In addition, rate of observation admissions and MACE were compared in the pre- and postintervention periods using piecewise regression and multiple logistic regression, respectively. Results: A total of 1422 patients were admitted for observation, and 290 were seen in CPC in the 1-year postintervention period. Thirty-day MACE was very low (0.7% in observation and 0.3% in CPC) postintervention. A total of 3637 patients were admitted for observation over the 2-year preintervention period. Thirty-day–adjusted MACE rate was not significantly different between pre- and postintervention periods (0.4% vs. 0.6%, P = 0.3), also monthly observation admissions did not change significantly; however, utilization of stress testing (57.2% vs. 41.0%, P < 0.001) and cardiac catheterization (2.3% vs. 1.6%, P = 0.036) was reduced. Conclusion: Chest pain patients admitted for observation and risk stratification are at very low risk of 30-day MACE. An intervention based on a chest pain protocol and availability of early cardiology follow-up did not change the admission rate of these patients. This intervention was not associated with increased risk of adverse outcomes.